ALTERNATIF PEMACUAN KINERJA PERSONEL DENGAN PENGELOLAAN KINERJA TERPADU BERBASIS BALANCED SCORECARD - Mulyadi, Mulyadi (Journal of Indonesian Economy and Business, 2005)
In this article I discussed a radical change in managing personnel performance. If inthe past, performances were measured only at responsibility center level and theperformance measures used were limited to financial measures, in this article I discussedhow to desain integrated performance management system for responsibility centers andpersonnel as well, using Balanced Scorecard as a basis. In this article, first I discussed thelimitation of executive performance measurement in traditional management. Then Iexplained expectancy theory created by Porter-Lawler to provide a conceptual frameworkin designing Balanced Scorecard based integrated performance management. In this article I discussed Balanced Scorecard based integrated performance management as analternative for driving personnel performance in building companyâs competitiveadvantage. At the end of this article I presented a summary of differences betweenperformance measurement in traditional management and that in modern management.Keywords: pengelolaan kinerja terpadu; balanced scorecard; kinerja